تكنولوجيا المعلومات و البيانات الضخمة (تطبيقات نظم المعلومات، أدوات ذكاء الأعمال والحوسبة السحابية دراسة تجارب - فريحة, سلمى (University of Eloued جامعة الوادي, 2022)
تعتبر البيانات الضخمة من أهم المواضيع البحثية في عالم اليوم، حيث تساهم في جودة اتخاذ القرار وتشكيل المعرفة في مختلف مجالات الحياة، إذ تمثل مرحلة هامة من مراحل تطور نظم وتقنية المعلومات والاتصالات التي من شأنه ا تسهم في التنمية الاقتصادية والاجتماعية، ومما لا شك فيه أن إمكانية الاستفادة من بيانات موجودة بالفعل في مؤسسة ما على نحو أفضل يمثل ميزة كبيرة لأي مؤسسة، إلا أن تقنيات معالجة البيانات الضخمة تصحبها تحديات تتعلق بالأمن والخصوصية، ورغم ذلك هناك العديد من الآليات التي تساعد البيانات الضخمة في تطويرها وتمكينها من توفير خدمات أفضل في المستقبل وتحسين عمليا ت اليومية ومواجهة التحديات والكوارث وBI الطبيعية وخلق فرص عمل بشكل أفض ل المتمثلة في تطبيق ات نظم المعلومات أ ودوات ذكاء الأعمال الحوسبة الحسابية التي توفر العديد من التقنيات المرنة و تقنية معاج لة كمية هائلة من البيانات . Abstract: Big data is one of the most important research topics in the world nowadays, It contribute to the quality of decision making and the development of knowledge in the various fields of life, as it represents an important stage in the development of information technology and communications systems that would contribute to the economic and social development, There is no doubt that the possibility of making use data already exit in an institution better represents a big advantage to any institution, But the big data processing techniques accompanied by challenges related to security and privacy, security and privacy, Although, there are many areas that Big data helps in their development and it enable them to provide better services in the future to improve the daily operations and challenges, nature disasters and the creation of employment opportunities for the better represented by: Information systems applications, business intelligence tools, and computational computing that provide many flexible techniques and technology for processing a huge amount of data.
Information technology and Big Data (Application of information systems, business intelligence and cloud computing)
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: البيانات الضخمة، معالجة البيانات، تطبيقات نظم المعلومات، ذكاء الأعمال BI ، الحوسبة السحابية; Big data, Information systems applications, business intelligence tools, and computational computing.